Tailoring the rheology, structural stability and printability of pea protein–κ-carrageenan hydrogels with Tremella fuciformis polysaccharide for 3D food printing - Hafiz Abdul Rasheed; Lei Wu; Abdur Rehman; Tabussam Tufail; Muhammad Waheed Iqbal; Ahsan Hafiz Muhammad; Ming Cai (Journal of Food Engineering, 2027)

In-Situ engineering of hierarchical ZIF@HOF heterostructures for efficient antibiotic degradation: Mechanistic insights from experimental and DFT studies - Ali Ahmad; Naeem Akram; Muhammad Khurram Tufail; Bing Yu; Hailin Cong (Water Research, 2027)

Plant-derived biopesticides for sustainable crop protection: Review and bibliometric mapping - Hamood U. Rehman; Norida Mazlan; Muhammad Shoaib Tufail (Food and Humanity, 2026)

Beyond mortality: A multi-outcome assessment of health economic benefits from air pollution control in China - Hao-Wen Liao; Zhi-Ming Han; Guo-Ping Dong; Duo-Hong Chen; Min Xie; Jun Liu; Junyu Zheng; Yun-Ting Zhang; Haseeb Tufail Moryani; Muhammad Amjad; Yang Zhou; Wen-Wen Bao; et al. (Environmental Research, 2026)

PFAS associated with dysglycemia and glucose trajectories: a prospective cohort study from the Isomers of C8 Health Project in China - Wen-Qi Yang; Yun-Ting Zhang; Wen-Yu Wang; Haseeb Tufail Moryani; Muhammad Amjad; Zeeshan Mohammed; Xuan Liu; Yan-Xu Chen; Kun Zhao; Chu Chu; Yang Zhou; Li-Zi Lin; et al. (Environmental Pollution, 2026)

Deciphering the role of potato peel on sunflower hybrids growth, photosynthesis, osmoregulation, oxidative defense and ion uptake under salinity - Sundas Fatima; Aasma Tufail; Muhammad Bilal Hafeez; Samreen Nazeer; Noreen Zahra; Fatima Latif; Sabina Asghar; Muhammad Ahsan; Muhammad Hamza; Muhammad Zubair Akram (Biocatalysis and Agricultural Biotechnology, 2026)

Towards eco-conscious cement production: a life cycle assessment model for ordinary portland cement manufacturing - Muhammad Burhan Memon; Ming Tao; Zheng Yang; Sami Ullah; Aimal Khan; Tufail Ahmed (Environment, Development and Sustainability, 2026)

Geochemical Characterization of Saidgai and Katora Lakes for Irrigation, Drinking, and Health Risk Indices, Hindu Kush Region - Said Muhammad; Tufail Ahmad; Wajid Ali; Adnan Ali Khan; Cem Tokatli; Ashfaq Ahmad; Zafar Iqbal (Water, Air, & Soil Pollution, 2026)

The first complete genome sequence of a highly pathogenic fowl adenovirus serotype 4 isolate from an infected chicken in Pakistan reveals the absence of a natural large genomic deletion - Salman Ahmad; Syeda Fakhra Waheed; Itra Ayoub; Ayesha Siddiqua; Soban Tufail; Sofia Irfan; Raheem Ullah; Muhammad Salahuddin Shah; Mazhar Iqbal; Moazur Rahman; Aamir Shehzad (Archives of Virology, 2026)

Deep eutectic solvent: a promising way to enhance the physicomechanical and antimicrobial properties of pullulan/carboxymethyl chitosan films impregnated with zein–nisin nanofillers for sustainable food packaging - Jawad Ashraf; Jiyao Zhang; Tabussam Tufail; Muhammad Awais; Shuyi liu; Yajing Qi; Zahoor Ahmed; Liming Yue; Zhou Sumei; Bin Xu (Food Hydrocolloids, 2026)

Evaluating the Accuracy of Machine Learning Models with Short-Term Lag Inputs for Univariate Daily Streamflow time Series Forecasting - Saad Ashfaq; Safia Waseem; Muhammad Tufail; Aqil Tariq (Water Resources Management, 2026)

Corrigendum to “Zein nanoparticles in emerging food packaging: Mechanistic insights into self-assembly, structural driving forces, and functional applications” [Trends in Food Science & Technology 167 (2026) 105447] - Jawad Ashraf; Jiyao Zhang; Tabussam Tufail; Muhammad SafiUllah Virk; Ma Yuling; Muhammad Awais; Zahoor Ahmed; Zhou Sumei; Bin Xu (Trends in Food Science & Technology, 2026)

Zein nanoparticles in emerging food packaging: Mechanistic insights into self-assembly, structural driving forces, and functional applications - Jawad Ashraf; Jiyao Zhang; Tabussam Tufail; Muhammad SafiUllah Virk; Ma Yuling; Muhammad Awais; Zahoor Ahmed; Zhou Sumei; Bin Xu (Trends in Food Science & Technology, 2026)

Roles of Wnt ligands and receptors in oral squamous cell carcinoma - Muhammad Tufail; Caiyun He; Canhua Jiang; Ning Li (Journal of Zhejiang University-SCIENCE B, 2025)

Tea (Camellia sinensis L.) anthocyanins and their compounded stability through conjugation: A promising instrument to synthesize green, halochromic, active and intelligent packaging - Muhammad Safiullah Virk; Muhammad Abdulrehman Virk; Mehak Gul; Shiyu Zhang; Tabussam Tufail; Xinzhuan Yao; Litang Lu (Trends in Food Science & Technology, 2025)

YY1 lactylation promotes fibroblast senescence by targeting the PU.1-BTG2 axis to promote oral submucous fibrosis - Muhammad Tufail; Jing Zhang; Cai-Yun He; Jia-Ju Hu; Jie Liang; Wen-Dong Wan; Yu-Qi Huang; Zhen Rao; Hong Wu; Can-Hua Jiang; Ning Li (Chemico-Biological Interactions, 2025)

Zinc-based nanoparticles improved the growth, chlorophyll, osmoregulation and ions relations of sunflower under combined shade and drought stress - Maria Tariq; Aasma Tufail; Muhammad Bilal Hafeez; Mafia Shoukat; Naeem Ahmad; Shahid Iqbal; Maqsood ul Hussan; Tayyaba Tariq; Muhammad Kamran; Muhammad Ahsan; Fahd Rasul; Noreen Zahra (Biocatalysis and Agricultural Biotechnology, 2025)

Flood susceptibility assessment and mapping using GIS-based analytical hierarchy process and frequency ratio models - Saad Ashfaq; Muhammad Tufail; Asif Niaz; Sher Muhammad; Hassan Alzahrani; Aqil Tariq (Global and Planetary Change, 2025)

Herbaceous plants reshape rhizosphere microbial communities and enhance nitrogen removal efficiency in riparian buffer zones: A quantitative study from simulated experiments - Chi Zhang; Xing Zheng; Xiaopeng Qiu; Tufail Muhammad; Mohan Wei; Kai Guo; Jiheng Duan; Menghan Wang; Xiangyao Yuan; Wenwei Ma; Xiaolin Li; Yaozhong Zhang; et al. (Rhizosphere, 2025)

Phytomining potential, micro-morphological assessment, and air pollution tolerance index of plant species in multi-metals contaminated soapstone and crushing stone mines - Tufail Shakeel; Ghulam Mujtaba Shah; Bibi Saima Zeb; Iram Gul; Muhammad Irshad; Habiba Zafar (Science of The Total Environment, 2025)

Towards greener metal production: A life cycle assessment model for copper-gold-silver mining and mineral processing operations - Muhammad Burhan Memon; Ming Tao; Tufail Ahmed; Zheng Yang; Muhammad Ibrahim; Sami Ullah (Process Safety and Environmental Protection, 2025)

Sustainable and contemporary approaches to explore the nutritional and processing perspectives of buckwheat: Current evidence and prospects - Zunaira Basharat; Tabussam Tufail; Feng Shao; Muhammad Safiullah Virk; Yuqing Duan; Meihong Cai; Kai Hu; Nisa Basharat; Haihui Zhang (Food Bioscience, 2025)

Promoting sustainable mining: A life cycle assessment model for small-scale underground chromite mining and processing operations - Muhammad Burhan Memon; Ming Tao; Sami Ullah; Zheng Yang; Tufail Ahmed; Shafi Muhammad Pathan (Journal of Cleaner Production, 2025)

Layer-by-layer concurrent encapsulation of probiotics and bioactive compounds with supplementation in intermediary layers: An establishing instrument for microbiome recharge, core safety, and targeted delivery - Muhammad Safiullah Virk; Muhammad Abdulrehman Virk; Mehak Gul; Muhammad Awais; Qiufang Liang; Tabussam Tufail; Mingming Zhong; Yufan Sun; Abdul Qayum; Ekram Abd El-Salam; John-Nelson Ekumah; Abdur Rehman; et al. (Food Hydrocolloids, 2025)

Assessing access to safe drinking water in flood-affected areas of District Nowshera, Pakistan: A case study towards achieving sustainable development goal 6.1 - Muhammad Tufail; Muhammad Jamal Nasir; Aqil Tariq; Zahid Ali; Saad S. Alarifi (Ecohydrology & Hydrobiology, 2025)

Exploring the Probiotic Potential of Bacteroides spp. Within One Health Paradigm - Muhammad Aammar Tufail; Ruth A. Schmitz (Probiotics and Antimicrobial Proteins, 2025)
Probiotics are pivotal in maintaining or restoring the balance of human intestinal microbiota, a crucial factor in mitigating diseases and preserving the host’s health. Exploration into Bacteroides spp. reveals substantial promise in their development as next-generation probiotics due to their profound interaction with host immune cells and capability to regulate the microbiome’s metabolism by significantly impacting metabolite production. These beneficial bacteria exhibit potential in ameliorating various health issues such as intestinal disorders, cardiovascular diseases, behavioral disorders, and even cancer. Though it’s important to note that a high percentage of them are as well opportunistic pathogens, posing risks under certain conditions. Studies highlight their role in modifying immune responses and improving health conditions by regulating lymphocytes, controlling metabolism, and preventing inflammation and cancer. The safety and efficacy of Bacteroides strains are currently under scrutiny by the European Commission for authorization in food processing, marking a significant step towards their commercialization. The recent advancements in bacterial isolation and sequencing methodologies, coupled with the integration of Metagenome-Assembled Genomes (MAGs) binning from metagenomics data, continue to unveil the potential of Bacteroides spp., aiding in the broader understanding and application of these novel probiotics in health and disease management.

GABA (γ-aminobutyric acid) enrichment and detection methods in cereals: Unlocking sustainable health benefits - Tabussam Tufail; Huma Bader Ul Ain; Muhammad Safiullah Virk; Jawad Ashraf; Zahoor Ahmed; Anees Ahmed Khalil; Amara Rasheed; Bin Xu (Food Chemistry, 2025)

Investigating the impact of enzyme diversity in producing edible bird nest protein hydrolysates: Techno-functional, structural, molecular docking, and in vitro digestibility - Rabia Kanwal; Abdur Rehman; Muhammad Irfan; Mian Shamas Murtaza; Tabussam Tufail; Mian Anjum Murtaza; Tawfiq Alsulami; Ibrahim Khalifa; Song Miao (Food Structure, 2025)

Enhancing storage, thermal, and gastroprotective viability of Lactiplantibacillus plantarum bilayer encapsulated in ultrasonically prepared gum and protein-based composites - Muhammad Safiullah Virk; Muhammad Abdulrehman Virk; Muhammad Awais; Qiufang Liang; Junxia Wang; Tabussam Tufail; Zafarullah Muhammad; Yufan Sun; Mingming Zhong; Abdul Qayum; Yongjun Zhao; John-Nelson Ekumah; et al. (Food Bioscience, 2025)

Potential of iron oxide-modified biochar in simultaneous mitigation of lead and nickel toxicity in wheat (Triticum aestivum L.) - Tufail Shah; Muhammad Kashif Irshad; Wasim Javed; Mahshab Sheraz; Atif Muhmood; Ali Noman; Maryam M. Alomran; Sang Soo Lee; Jianying Shang (South African Journal of Botany, 2024)

Addressing resource curse: How mineral resources influence industrial structure dynamics of the BRI 57 oil-exporting countries - Tufail Muhammad; Guohua Ni; Zhenling Chen; Sabrine Mallek; Marek Dudek; Grzegorz Mentel (Resources Policy, 2024)

Linking green transportation and technology, and environmental taxes for transport carbon emissions - Mushtaq Ahmad; Zhang Jida; Izhar Ul Haq; Muhammad Tufail; Shah Saud (Transportation Research Part D: Transport and Environment, 2024)

Servant leadership and citizenship behavior in the Pakistani tourism and hospitality industry: The role of harmonious environmental passion and a green work climate - Yasir Iftikhar; Muhammad Shahid Tufail; Marcos Ferasso; Rizwan Qaiser Danish (Journal of Environmental Management, 2024)

Asymmetric effects of high-tech industry and presence of pollution-haven hypothesis in APEC countries: fresh evidence with panel quantile regression - Qasim Raza Khan; Ahsan Anwar; Tufail Muhammad; Noorulhaq Ghafoori; Mushtaq Ahmad (Clean Technologies and Environmental Policy, 2024)

Life cycle assessment model for small-scale coal mining operations with equivalent coal output: a greener perspective towards coal mining - Muhammad Burhan Memon; Ming Tao; Zheng Yang; Tufail Ahmed; Muhammad Ibrahim (Environment, Development and Sustainability, 2024)

Facilitated transport of ferrihydrite with phosphate under saturated flow conditions - Tufail Shah; Kang Zhao; Ai Chen; Atif Muhmood; Syed Atizaz Ali Shah; Muhammad Kashif Irshad; Yuji Arai; Jianying Shang (Journal of Contaminant Hydrology, 2024)

Enhancing storage and gastroprotective viability of Lactiplantibacillus plantarum encapsulated by sodium caseinate-inulin-soy protein isolates composites carried within carboxymethyl cellulose hydrogel - Muhammad Safiullah Virk; Muhammad Abdulrehman Virk; Qiufang Liang; Yufan Sun; Mingming Zhong; Tabussam Tufail; Arif Rashid; Abdul Qayum; Abdur Rehman; John-Nelson Ekumah; Junxia Wang; Yongjun Zhao; et al. (Food Research International, 2024)

Targeting PI3K/AKT/mTOR signaling to overcome drug resistance in cancer - Muhammad Tufail; Wen-Dong Wan; Canhua Jiang; Ning Li (Chemico-Biological Interactions, 2024)

Cu-TiO2-Aluminosilicate Nanocomposite as Highly Efficient Photocatalyst for Sustainable Removal of Cefixime Antibiotic: Synthesis, Optimization, and Toxicity Evaluation - Muhammad Umar Farooq; Qurat-Ul-Ain; Muhammad Irfan Jalees; Mahnoor Abid; Mirza Nadeem Ahmad; Maira Kaleem; Asma Tufail Shah; Juan Joon Ching (Environmental Processes, 2024)

Fundamental opportunities and challenges of nutraceutical noodles enriched with agri-food by-products - Zahoor Ahmed; Jin Chen; Tabussam Tufail; Anam Latif; Muhammad Arif; Riaz Ullah; Ali S. Alqahtani; Bin Xu (Trends in Food Science & Technology, 2024)

Added value upshot of barley amalgamation in wheat flour to boost the physico-chemical quality attributes of flat bread - Muhammad Abdullah; Muhammad Zulkiffal; Tabussam Tufail; Farah Naz Akbar; Muhammad Owais; Javed Ahmed; Ahsan Javed; Muhammad Ijaz Tabassum; Amna Kanwal; Muhammad Asghar; Muhammad Musa; M. A. Rehman Arif; et al. (Cereal Research Communications, 2023)

Selective capture of uranium and zirconium from strong HNO3 solution by ethenylphosphonic acid copolymerized polymer - Muhammad Hammad ul Haq; Xu Zhang; Fengqi Zhang; Alemtsehay Tesfay Reda; Dongxiang Zhang; Muhammad Zahid; Muhammad Khurram Tufail; Muhire Constantin; Noor Hasaan; Jinying Li; Xiyan Xu (Chemical Engineering Journal, 2023)

Green finance policy and heavy pollution enterprises: a supply-chain and signal transmission of green credit policy for the environment—Vietnam perspective - Chun-Wei Chen; Junxiong Zheng; Tin-Chang Chang; Muhammad Sadiq; Bushra Tufail (Environment, Development and Sustainability, 2023)

A new sesquiterpene, prosoterpene, from Prosopis africana (Guill. & Perr.) Taub - Raza Ali; Kayode Muritala Salawu; Muhammad Aamer; Humera Jahan; Priya Tufail; Rimsha Irshad; Farooq-Ahmad Khan; Bilge Sener; M. Iqbal Choudhary; Yan Wang (Natural Product Research, 2023)

Green financing strategy for low-carbon economy: The role of high-technology imports and institutional strengths in China - Taimoor Hassan; Yasir Khan; Adnan Safi; He Chaolin; Salman Wahab; Abdul Daud; Muhammad Tufail (Journal of Cleaner Production, 2023)

Enhancement in anaerobic biogas conversion by visible light photocatalytic Pre-treatment of rice husk with indium vanadate decorated titanium dioxide nanocomposite - Jamshaid Rashid; Talha Tufail Bhatti; Muhammad Hassan; M.A. Barakat; Rajeev Kumar; Ming Xu (Fuel, 2023)

WNT5A: a double-edged sword in colorectal cancer progression - Muhammad Tufail; Changxin Wu (Mutation Research - Reviews in Mutation Research, 2023)

A step toward sustainable development: the nexus of environmental sustainability, technological advancement and green finance: evidence from Indonesia - FengSheng Chien; Ching-Chi Hsu; Massoud Moslehpour; Muhammad Sadiq; Bushra Tufail; Thanh Quang Ngo (Environment, Development and Sustainability, 2023)

Mediation of gaseous emissions and improving plant productivity by DCD and DMPP nitrification inhibitors: Meta-analysis of last three decades - Muhammad Aammar Tufail; Muhammad Irfan; Wajid Umar; Abdul Wakeel; Ruth A. Schmitz (Environmental Science and Pollution Research, 2023)
Nitrification inhibitors (NIs), especially dicyandiamide (DCD) and 3,4-dimethylpyrazole phosphate (DMPP), have been extensively investigated to mitigate nitrogen (N) losses from the soil and thus improve crop productivity by enhancing N use efficiency. However, to provide crop and soil-specific guidelines about using these NIs, a quantitative assessment of their efficacy in mitigating gaseous emissions, worth for nitrate leaching, and improving crop productivity under different crops and soils is yet required. Therefore, based upon 146 peer-reviewed research studies, we conducted a meta-analysis to quantify the effect of DCD and DMPP on gaseous emissions, nitrate leaching, soil inorganic N, and crop productivity under different variates. The efficacy of the NIs in reducing the emissions of CO 2 , CH 4 , NO, and N 2 O highly depends on the crop, soil, and experiment types. The comparative efficacy of DCD in reducing N 2 O emission was higher than the DMPP under maize, grasses, and fallow soils in both organic and chemical fertilizer amended soils. The use of DCD was linked to increased NH 3 emission in vegetables, rice, and grasses. Depending upon the crop, soil, and fertilizer type, both the NIs decreased nitrate leaching from soils; however, DMPP was more effective. Nevertheless, the effect of DCD on crop productivity indicators, including N uptake, N use efficiency, and biomass/yield was higher than DMPP due to certain factors. Moreover, among soils, crops, and fertilizer types, the response by plant productivity indicators to the application of NIs ranged between 35 and 43%. Overall, the finding of this meta-analysis strongly suggests the use of DCD and DMPP while considering the crop, fertilizer, and soil types. Graphical Abstract

Nerium oleander could be used for sustainable management of traffic-borne elemental-enriched roadside soils - Noreen Khalid; Ali Noman; Atia Nazir; Aasma Tufail; Naila Hadayat; Fahad Mohammed Alzuaibr; Sobia Ikram; Noreen Akhter; Mumtaz Hussain; Muhammad Aqeel (Environmental Science and Pollution Research, 2023)

How ICT and globalization interact with the environment: a case of the Chinese economy - Munaza Bibi; Muhammad Kamran Khan; Muhammad Mutasim Billah Tufail; Danish Iqbal Godil; Rimsha Usman; Muhammad Faizan (Environmental Science and Pollution Research, 2023)

Groundwater quality assessment and its vulnerability to pollution: a study of district Nowshera, Khyber Pakhtunkhwa, Pakistan - Muhammad Jamal Nasir; Muhammad Tufail; Tehreem Ayaz; Sardar Khan; Amir Zeb Khan; Ming Lei (Environmental Monitoring and Assessment, 2022)

Moisture- and period-dependent interactive effects of plant growth-promoting rhizobacteria and AM fungus on water use and yield formation in dryland wheat - Muhammad Maqsood Ur Rehman; Ying Zhu; Muhammad Abrar; Wasim Khan; Wei Wang; Awais Iqbal; Anum Khan; Yuan Chen; Muhammad Rafiq; Muhammad Aammar Tufail; Jian-Sheng Ye; You-Cai Xiong (Plant and Soil, 2022)

The nexus between CO2 emissions, human capital, technology transfer, and renewable energy: evidence from Belt and Road countries - Yasir Khan; Taimoor Hassan; Muhammad Tufail; Mohamed Marie; Muhammad Imran; Zhang Xiuqin (Environmental Science and Pollution Research, 2022)

Change in forest biomass with altitudinal variations in dry temperate forest of Dir Kohistan, Pakistan - Syed Tufail Ahmad; Ahmad Hussain; Saif Ullah; Aitezaz Muhammad Khan; Muhammad Sadiq Khan; Inam Ullah (Modeling Earth Systems and Environment, 2022)

DNA barcoding and population genetic structure of the red palm weevil, Rhynchophorus ferrugineus (Coleoptera: Curculionidae) in Egypt based on mtDNA sequencing - Maged M. A. Fouda; Muhammad Tufail; Makio Takeda; Shaymaa H. Mahmoud (Biologia, 2022)

Deep learning-based identification system of weeds and crops in strawberry and pea fields for a precision agriculture sprayer - Shahbaz Khan; Muhammad Tufail; Muhammad Tahir Khan; Zubair Ahmad Khan; Shahzad Anwar (Precision Agriculture, 2021)

Do fiscal decentralization and natural resources rent curb carbon emissions? Evidence from developed countries - Muhammad Tufail; Lin Song; Tomiwa Sunday Adebayo; Dervis Kirikkaleli; Suliman Khan (Environmental Science and Pollution Research, 2021)

Correction to: Elucidating the distinct interactive impact of cadmium and nickel on growth, photosynthesis, metal-homeostasis, and yield responses of mung bean (Vigna radiata L.) varieties - Muhammad Aqeel; Noreen Khalid; Aasma Tufail; Rana Zaheer Ahmad; Muhammad Salim Akhter; Muhammad Luqman; Muhammad Tariq Javed; Muhammad Kashif Irshad; Saad Alamri; Mohamed Hashem; Ali Noman (Environmental Science and Pollution Research, 2021)

Elucidating the distinct interactive impact of cadmium and nickel on growth, photosynthesis, metal-homeostasis, and yield responses of mung bean (Vigna radiata L.) varieties - Muhammad Aqeel; Noreen Khalid; Aasma Tufail; Rana Zaheer Ahmad; Muhammad Salim Akhter; Muhammad Luqman; Muhammad Tariq Javed; Muhammad Kashif Irshad; Saad Alamri; Mohamed Hashem; Ali Noman (Environmental Science and Pollution Research, 2021)

Nexus on climate change: agriculture and possible solution to cope future climate change stresses - Aqeel Shahzad; Sana Ullah; Afzal Ahmed Dar; Muhammad Fahad Sardar; Tariq Mehmood; Muhammad Aammar Tufail; Awais Shakoor; Muhammad Haris (Environmental Science and Pollution Research, 2021)

Comparative Response of Two Rice (Oryza sativa L.) Cultivars to Applied Zinc and Manganese for Mitigation of Salt Stress - Faisal Nadeem; Muhammad Azhar; Muhammad Anwar-ul-Haq; Muhammad Sabir; Tayyaba Samreen; Abdullah Tufail; Hafiz Umair Masood Awan; Wu Juan (Journal of Soil Science and Plant Nutrition, 2020)

Diversity of red palm weevil, Rhynchophorus ferrugineus Oliv. (Coleoptera: Curculionidae) in the Kingdom of Saudi Arabia: studies on the phenotypic and DNA barcodes - Sukirno Sukirno; Muhammad Tufail; Khawaja Ghulam Rasool; Mureed Husain; Abdulrahman Saad Aldawood (International Journal of Tropical Insect Science, 2020)

The Effect of Encapsulation on The Stability of Probiotic Bacteria in Ice Cream and Simulated Gastrointestinal Conditions - Muhammad Afzaal; Farhan Saeed; Muhammad Umair Arshad; Muhammad Tahir Nadeem; Muhammad Saeed; Tabussam Tufail (Probiotics and Antimicrobial Proteins, 2019)

Composting of municipal solid waste by different methods improved the growth of vegetables and reduced the health risks of cadmium and lead - Ghulam Mustafa Shah; Nadia Tufail; Hafiz Faiq Bakhat; Iftikhar Ahmad; Muhammad Shahid; Hafiz Mohkum Hammad; Wajid Nasim; Atika Waqar; Muhammad Rizwan; Renjie Dong (Environmental Science and Pollution Research, 2019)

Effectiveness of carbon dioxide against different developmental stages of Cadra cautella and Tribolium castaneum - Mureed Husain; Sukirno Sukirno; Khalid Mehmood; Muhammad Tufail; Khawaja Ghulam Rasool; Waleed Saleh Alwaneen; Abdulrahman Saad Aldawood (Environmental Science and Pollution Research, 2017)

Banana peel: an effective biosorbent for aflatoxins - Zahid Hussain Shar; Mary T. Fletcher; Gul Amer Sumbal; Syed Tufail Hussain Sherazi; Cindy Giles; Muhammad Iqbal Bhanger; Shafi Muhammad Nizamani (Food Additives & Contaminants: Part A, 2016)

Elemental contamination in urban parks of Rawalpindi/Islamabad—a source identification and pollution level assessment study - Sajid Iqbal; Mohammad Wasim; Muhammad Tufail; Mohammad Arif; Muhammad M. Chaudhry (Environmental Monitoring and Assessment, 2012)

Radium equivalent activity in the light of UNSCEAR report - Muhammad Tufail (Environmental Monitoring and Assessment, 2012)

Assessment of radiological hazard of NORM in Margalla Hills limestone, Pakistan - Muhammad Ali; Aziz Ahmed Qureshi; Abdul Waheed; Muzahir Ali Baloch; Hamza Qayyum; Muhammad Tufail; Hameed Ahmed Khan (Environmental Monitoring and Assessment, 2012)

Differential expression of vitellogenin mRNA and protein in response to rice resistance genes in two strains of Nilaparvata lugens (Hemiptera: Delphacidae) with different levels of virulence - Nirosha Samanmali Gamalath; Muhammad Tufail; Prem Nidhi Sharma; Naoki Mori; Makio Takeda; Chiharu Nakamura (Applied Entomology and Zoology, 2012)

Hormonal regulation and effects of four environmental pollutants on vitellogenin gene transcription in the giant water bFfigug, Lethocerus deyrollei (Hemiptera: Belostomatidae) - Yoshiki Nagaba; Muhammad Tufail; Hideyuki Inui; Makio Takeda (Journal of Insect Conservation, 2011)

Transfer of radioactivity from soil to vegetation in Rechna Doab, Pakistan - Abdul Jabbar; Muhammad Tufail; Waheed Arshed; Arshed Salem Bhatti; Syed Salman Ahmad; Perveen Akhter; Muhammad Dilband (Isotopes in Environmental and Health Studies, 2010)